Intranasal HSP70 administration protects against dopaminergic denervation and modulates neuroinflammatory response in the 6-OHDA rat model - Camila Tiefensee Ribeiro; Daniel Oppermann Peixoto; Lucas Santos; Carolina Saibro-Girardi; Pedro Ozorio Brum; Flávio Gabriel Carazza-Kessler; Nauana Somensi; Luiza Marques Prates Behrens; Reykla Ramon Bittencourt; Laíssa Santos Soares; Alexandre Kleber Silveira; Jade de Oliveira; et al. (Brain, Behavior, & Immunity - Health, 2021)
HSP70 is one of the main molecular chaperones involved in the cellular stress response. Besides its chaperone action, HSP70 also modulates the immune response. Increased susceptibility to toxic insults in intra- and extracellular environments has been associated with insufficient amounts of inducible HSP70 in adult neurons. On the other hand, exogenous HSP70 administration has demonstrated neuroprotective effects in experimental models of age-related disorders. In this regard, this study investigated the effects of exogenous HSP70 in an animal model of dopaminergic denervation of the nigrostriatal axis. After unilateral intrastriatal injection with 6-hydroxydopamine (6-OHDA), the animals received purified recombinant HSP70 through intranasal administration (2 μg/rat/day) for 15 days. Our results indicate a neuroprotective effect of intranasal HSP70 against dopaminergic denervation induced by 6-OHDA. Exogenous HSP70 improved motor impairment and reduced the loss of dopaminergic neurons caused by 6-OHDA. Moreover, HSP70 modulated neuroinflammatory response in the substantia nigra, an important event in Parkinson’s disease pathogenesis. Specifically, HSP70 treatment reduced microglial activation and astrogliosis induced by 6-OHDA, as well as IL-1β mRNA expression in this region. Also, recombinant HSP70 increased the protein content of HSP70 in the substantia nigra of rats that received 6-OHDA. These data suggest the neuroprotection of HSP70 against dopaminergic neurons damage after cellular stress. Finally, our results indicate that HSP70 neuroprotective action against 6-OHDA toxicity is related to inflammatory response modulation.